Space optical payload cable based on carbon-based materials and preparation method thereof

Through the aerospace optical load cable made of carbon-based materials, the problems of traditional metal conductor cables are solved, with limited electromagnetic shielding effect and easy damage in extreme environments, and the cable is lightweight, durable and efficient electromagnetic shielding, extending service life and reducing matte interference.

CN119480227BActive Publication Date: 2025-04-08CHANGCHUN INST OF OPTICS FINE MECHANICS & PHYSICS CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510055239.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-08
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

Traditional metal conductor cables have large weight and limited electromagnetic shielding effects. They are prone to fatigue, fracture, and aging failure in extreme environments. The high surface reflectivity leads to light interference, affecting the optical performance of the system.

Method used

The aerospace optical load cable made of carbon-based materials is the structure from the inside to the outside, including a stranded conductor, a polyimide insulating layer, a graphene shielding layer, a ceramic-based composite material barrier layer, a Teflon outer sheath and a low reflectivity extinction layer.

Benefits of technology

It significantly reduces the weight of the cable, improves ductility and fatigue resistance, enhances electromagnetic shielding effect and radiation resistance, extends the service life of the cable, and effectively reduces the matte interference in the optical load system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480227B_ABST
    Figure CN119480227B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of cables, and in particular to a space optical load cable based on carbon-based materials and a preparation method thereof, wherein the cable comprises a twisted conductor, a polyimide insulation layer, a graphene shielding layer, a ceramic-based composite barrier layer, a Teflon outer sheath and a low-reflectivity extinction layer from the inside to the outside; wherein the twisted conductor comprises a carbon nanotube cable core and a graphite-reinforced polymer cable core; and the low-reflectivity extinction layer comprises a black oxide material layer and a carbon-based material layer located outside the black oxide material layer. The present invention provides uniform pressure to the bonding surface through the atmospheric pressure difference, ensures that the high thermal conductivity material is tightly combined with the complex curved surface structure, avoids the generation of bubbles at the bonding point due to uneven pressure, and significantly improves the bonding strength and bonding quality; at the same time, the bonding time is effectively shortened and the bonding efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cables, and in particular relates to a carbon-based material-based aerospace optical load cable and a preparation method thereof. Background Art

[0002] At present, spacecraft usually use metal conductor cables to achieve data transmission and power supply. Metal conductor cables are widely used in satellites, deep space probes and manned spacecraft. Metal conductor cables usually use copper or aluminum as conductive materials. The density of copper and aluminum is 8.96g / cm³ and 2.70g / cm³ respectively. Although metal conductor cables have good conductivity, the high density makes the weight of metal conductor cables relatively large, which increases the total mass of the spacecraft and increases the launch cost. In addition, metal conductor cables are prone to fatigue and breakage in extreme environments (such as high temperature, low temperature, space radiation, etc.); the shielding materials of metal conductor cables cannot fully resist external electromagnetic interference; and the outer sheath materials of metal conductor cables are prone to aging, cracking or performance degradation in harsh environments such as high temperature and radiation, which affects the overall performance and life of the cable. At the same time, traditional metal cables in optical payload systems will also cause stray light interference due to high surface reflectivity, affecting the optical performance of the system. For example, in some missions, metal conductor cables break conductors or age the insulation layer in high temperature environments, resulting in system failure. This type of failure is particularly critical in manned spacecraft and deep space probes. Summary of the invention

[0003] In view of this, the present invention aims to provide a space optical payload cable based on carbon-based materials and a preparation method thereof, so as to solve the problems that traditional metal conductor cables are heavy, have limited electromagnetic shielding effect, are prone to fatigue, breakage, aging failure in extreme environments, and have high surface reflectivity leading to stray light interference, affecting the optical performance of the system.

[0004] To achieve the above object, the technical solution created by the present invention is implemented as follows:

[0005] A space optical payload cable based on carbon-based materials comprises, from inside to outside, a twisted conductor, a polyimide insulation layer, a graphene shielding layer, a ceramic-based composite barrier layer, a Teflon outer sheath and a low-reflectivity extinction layer; wherein the twisted conductor comprises a carbon nanotube cable core and a graphite-reinforced polymer cable core; the low-reflectivity extinction layer comprises a black oxide material layer and a carbon-based material layer located outside the black oxide material layer.

[0006] Furthermore, the black oxide material layer is Fe3O4, and the carbon-based material layer is graphene or carbon nanotubes.

[0007] Furthermore, the thickness of the black oxide material layer is 50 nm to 150 nm.

[0008] A method for preparing the above-mentioned carbon-based material-based aerospace optical payload cable comprises the following steps:

[0009] S1: Processing carbon nanotubes and graphite-reinforced polymers into yarn or sheet form and spirally winding them to form a stranded conductor;

[0010] S2: A polyimide film is wrapped around the outside of the stranded conductor using a hot melt process to form a polyimide insulation layer;

[0011] S3: A graphene shielding layer is formed by wrapping a layer of graphene film on the outside of the polyimide insulating layer by physical vapor deposition or electrostatic spraying process;

[0012] S4: using bonding technology or surface treatment process to coat the ceramic-based composite material on the outside of the graphene shielding layer to form a ceramic-based composite material barrier layer;

[0013] S5: The Teflon material is processed into a Teflon outer sheath by an extrusion molding process, and is wrapped around the outer side of the ceramic matrix composite barrier layer;

[0014] S6: spraying a black oxide material on the surface of the Teflon outer sheath by an electrostatic spraying process to form a black oxide material layer, and then applying a layer of nanostructured carbon-based material on the black oxide material layer to form a carbon-based material layer.

[0015] Furthermore, it is characterized in that the number of carbon nanotubes and graphite reinforced polymers are 10 to 20 respectively.

[0016] Furthermore, the winding angle of the carbon nanotubes and the graphite-reinforced polymer is 25° to 35°.

[0017] Furthermore, during the winding process of the carbon nanotubes and the graphite-reinforced polymer, a tensile prestress of 5 MPa to 20 MPa is applied to the carbon nanotubes and the graphite-reinforced polymer.

[0018] Furthermore, the process parameters of the hot melt process are: hot melt temperature is 400°C, coating time is 30min, and pressure is 5MPa.

[0019] Furthermore, the black oxide material is sprayed in a vacuum or under specific electrostatic conditions by using physical vapor deposition or electrostatic spraying technology.

[0020] Compared with the prior art, the invention can achieve the following beneficial effects:

[0021] 1. By using carbon nanotubes as the conductor material of the cable, the weight of the cable is significantly reduced, and the ductility and fatigue resistance of the cable are improved compared with traditional metal conductors.

[0022] 2. Compared with polyvinyl chloride (PVC) insulation layer, polyimide insulation material can still maintain good insulation performance in high temperature environment (above 300°C), while PVC will begin to soften and lose insulation at 200°C. Compared with polytetrafluoroethylene (PTFE) insulation layer, polyimide insulation layer has better dielectric strength and thermal stability, making it perform particularly well in harsh aerospace environments.

[0023] 3. The graphene shielding layer attenuates electromagnetic interference by more than 85% in the frequency range of 1GHz to 10GHz, which is significantly better than the electromagnetic shielding effect of traditional metal shielding materials.

[0024] 4. The ceramic-based composite barrier layer significantly improves the cable's adaptability in extreme high temperature environments, ensuring the stability of signal transmission.

[0025] 5. Compared with other outer sheath materials, such as silicone rubber and polyvinyl chloride (PVC), Teflon outer sheath can not only remain stable at higher temperatures (up to 260°C), but also has better radiation resistance and chemical corrosion resistance. These characteristics make Teflon outer sheath particularly suitable for use in aerospace environments that require extreme temperature tolerance and high reliability, ensuring that the cable can still operate stably under long-term exposure to high temperature and strong radiation conditions.

[0026] 6. The low reflectivity extinction layer located on the outermost layer can effectively reduce stray light in optical payload applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments and descriptions of the present invention are used to explain the present invention and do not constitute an improper limitation on the present invention. In the drawings:

[0028] Figure 1 It is a schematic diagram of the structure of a carbon-based material-based aerospace optical payload cable according to an embodiment of the invention.

[0029] Explanation of the reference numerals: twisted conductor 1, carbon nanotube cable core 1-1, graphite reinforced polymer cable core 1-2, insulation layer 2, graphene shielding layer 3, ceramic-based composite barrier layer 4, Teflon outer sheath 5, low-reflectivity extinction layer 6. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the invention more clear, the invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described here are only used to explain the invention and do not constitute a limitation of the invention.

[0031] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0032] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0033] In the description of the invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installation", "connection" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the invention can be understood according to specific circumstances.

[0034] The following will refer to the attached Figure 1 The invention is described in detail with reference to the embodiments.

[0035] like Figure 1 As shown, the aerospace optical load cable based on carbon-based materials provided by the embodiment of the invention includes a twisted conductor 1, a polyimide insulation layer 2, a graphene shielding layer 3, a ceramic-based composite barrier layer 4, a Teflon outer sheath 5 and a low-reflectivity extinction layer 6 wrapped in sequence from the inside to the outside.

[0036] Stranded conductor 1: The core conductive part of the cable adopts a carbon nanotube (CNT) cable core 1-1. Compared with traditional copper conductors, the carbon nanotube cable core has extremely high conductivity and strength, and its weight is greatly reduced, which can significantly reduce the overall weight of the cable. In addition, the present invention also introduces a graphite enhanced polymer (GEP) cable core 1-2 for composite use with the carbon nanotube cable core 1-1. The graphite enhanced polymer cable core 1-2 can improve the mechanical strength and conductivity of the cable, especially by optimizing the winding angle. The inner layer of the graphite enhanced polymer cable core 1-2 enhances the mechanical strength with a larger winding angle, and the outer layer of the carbon nanotube cable core 1-1 enhances the conductivity with a smaller winding angle, thereby achieving a higher performance balance. This combination significantly improves the durability, lightness and electrical performance of the cable. Carbon nanotubes are a nanomaterial with high strength, high conductivity and lightness. A copper wire with a length of 1 meter and a cross-sectional area of ​​1 mm² can weigh up to 8.96 grams, while the weight of a carbon nanotube cable core conductor with the same cross-sectional area is only one-third of that of a copper wire. The ductility and tensile strength of carbon nanotube cable cores far exceed those of traditional metal materials. For example, experiments have shown that the tensile strength of carbon nanotube cable cores can reach 30GPa~60GPa, which is dozens of times that of traditional copper materials. At the same time, the conductivity of carbon nanotube cable cores can reach 1.00S / cm*10 under laboratory conditions. 6 S / cm.

[0037] The weight reduction effect brought by the carbon nanotube cable core 1-1 directly reduces the launch cost of the spacecraft, and each kilogram of weight reduction can save about $20,000 in launch costs. In addition, due to the reduction in cable weight, the spacecraft can carry more payload, thereby improving the overall efficiency of the mission. It also reduces the launch cost of the spacecraft and increases the load capacity. The high ductility of the carbon nanotube cable core 1-1 enables the cable to maintain good structural integrity and conductive properties under conditions of multiple bending and vibration. This high ductility greatly improves the service life and reliability of the cable.

[0038] The performance comparison of carbon nanotubes, copper, aluminum, and graphene is shown in Table 1:

[0039] Table 1 Performance comparison of carbon nanotubes, copper, aluminum, and graphene as cable cores

[0040]

[0041] Polyimide insulation layer 2: A polyimide insulation layer 2 is formed by wrapping a polyimide film on the outside of the twisted conductor 1. Polyimide is a material with excellent insulation properties and high temperature resistance, and can maintain stable electrical properties under extreme temperature conditions. Compared with commonly used insulating materials such as polyvinyl chloride (PVC) and polytetrafluoroethylene (PTFE), polyimide can still maintain good insulation properties in high temperature environments (above 300°C), while PVC begins to soften and lose insulation at 200°C. Compared with PTFE, polyimide also has better dielectric strength and thermal stability, making it particularly excellent in harsh aerospace environments. The polyimide insulation layer 2 ensures the safety of the cable and prevents current leakage and short circuits.

[0042] Graphene shielding layer 3: A graphene film is coated on the outside of the polyimide insulating layer 2 to form a graphene shielding layer 3, and the thickness of the graphene shielding layer 3 ranges from 30nm to 50nm. Graphene coated on the outside of the polyimide insulating layer 2 can effectively resist external electromagnetic interference and ensure the stability of signal transmission. In addition, the high conductivity of the graphene film helps to quickly guide external electromagnetic waves and play a good shielding role. The graphene film is thin and strong, which further reduces the weight of the cable.

[0043] Ceramic-based composite barrier layer 4: The ceramic-based composite material is coated on the outside of the graphene shielding layer 3 to form a ceramic-based composite barrier layer 4. The ceramic-based composite barrier layer 4 mainly further enhances the cable's radiation resistance and thermal insulation performance to effectively isolate thermal radiation and protect the internal structure under high radiation conditions. The introduction of the ceramic-based composite barrier layer 4 significantly improves the cable's adaptability in extreme high temperature environments and ensures the stability of signal transmission.

[0044] Teflon outer sheath 5: Teflon material has excellent high temperature resistance, radiation resistance and corrosion resistance, and can provide long-term protection for cables in harsh aerospace environments, ensuring the long-term service life of cables under harsh conditions such as high temperature and radiation. Compared with other possible materials, such as silicone rubber and polyvinyl chloride (PVC), Teflon can not only remain stable at higher temperatures (up to 260°C), but also has better radiation resistance and chemical corrosion resistance. These characteristics make it particularly suitable for use in aerospace environments that require extreme temperature tolerance and high reliability, ensuring that the cable can still operate stably under long-term exposure to high temperature and strong radiation conditions.

[0045] Low reflectivity extinction layer 6: Mainly used to reduce stray light reflection in cables in optical load applications. In order to achieve the best light absorption effect, the low reflectivity extinction layer 6 adopts a double-layer composite structure. First, the black oxide material (Fe3O4) is sprayed on the surface of the Teflon outer sheath 5 by an electrostatic spraying process. Through the action of electrostatic charge, the charged oxide particles are evenly sprayed onto the Teflon outer sheath 5 with the opposite charge, forming a uniform, low-reflectivity black oxide material layer to absorb the main incident light. Then, a layer of nanostructured carbon-based material (such as graphene or carbon nanotubes) is applied on the black oxide material layer to form a carbon-based material layer. The carbon-based material layer can not only absorb the remaining light energy, but also make the incident light reflect and scatter multiple times on a microscopic scale through its special nanostructure, thereby further reducing the reflectivity.

[0046] The above content describes in detail the structure of the carbon-based material-based aerospace optical payload cable provided by the inventive embodiment of the present invention. Corresponding to the cable structure, the inventive embodiment of the present invention also provides a method for preparing the cable structure.

[0047] The method for preparing a carbon-based material-based aerospace optical payload cable provided by the present invention comprises the following steps:

[0048] S1: Processing carbon nanotubes and graphite-reinforced polymers into yarn or sheet forms to form a carbon nanotube cable core 1-1 and a graphite-reinforced polymer cable core 1-2, which are spirally wound to form a stranded conductor 1.

[0049] By optimizing the winding angles of the carbon nanotube cable core 1-1 and the graphite reinforced polymer cable core 1-2, both the mechanical strength and the conductivity of the cable are taken into consideration.

[0050] (1) Multi-strand winding structure: The carbon nanotube cable core 1-1 and the graphite reinforced polymer cable core 1-2 adopt a multi-strand structure, usually consisting of 10 to 20 strands, which greatly improves the electrical conductivity and mechanical strength of the cable while keeping the cable light. The multi-strand winding method helps the cable maintain stable conductivity during multiple bending and vibration processes.

[0051] (2) Winding angle: The carbon nanotube cable core 1-1 and the graphite reinforced polymer cable core 1-2 are wound in a spiral manner. During the winding process, the winding angle is one of the important factors to ensure that the carbon nanotube cable core 1-1 and the graphite reinforced polymer cable core 1-2 are evenly distributed. A small winding angle (10°~20°) formed with the cable axis is conducive to enhancing the electrical conductivity of the cable, while a large winding angle (30°~45°) formed with the cable axis is conducive to improving the mechanical strength of the cable. Taking into account the electrical conductivity and tensile strength, a winding angle of 25°~35° is adopted, which not only maintains high electrical conductivity but also has excellent tensile resistance.

[0052] The winding angle can be calculated using the following empirical formula: ; where θ is the winding angle, p is the winding pitch (i.e. the axial distance between adjacent coils), and D is the diameter of the winding layer. A reasonable winding angle can ensure uniform distribution of the cable core on the cable and avoid performance problems caused by stress concentration and uneven winding.

[0053] (3) Fiber prestressing: During the winding process, appropriate prestressing needs to be applied, generally in the range of 5MPa to 20MPa, to ensure that the tension of the winding cable core remains consistent and to avoid relaxation or breakage during operation. Winding the cable core after it has been stretched to a certain extent can enable the cable to maintain high mechanical properties and long life under working conditions.

[0054] High-purity carbon nanotubes are prepared by chemical vapor deposition (CVD) and processed into yarn or sheet form. The difficulty of this process is to ensure the high purity and consistency of the carbon nanotubes. Any impurities will significantly affect the conductivity and mechanical properties of the material. In addition, the processing of carbon nanotubes into yarns or sheets requires precise control to ensure the ductility and tensile strength of the final conductor. There are also challenges in the multi-strand winding method. It is necessary to ensure that the tension of each yarn is uniform, otherwise it will affect the conductive performance and structural stability.

[0055] S2: A polyimide film is wrapped around the outer side of the stranded conductor by a hot-melt process to form a polyimide insulation layer 2.

[0056] The process parameters of the hot melt process are: hot melt temperature is 400° C., coating time is 30 min, and pressure is controlled at about 5 MPa. This process can ensure the uniformity of the polyimide insulation layer 2 and its stable performance in a high temperature environment.

[0057] During the wrapping process, the thickness and uniformity of the polyimide film need to be strictly controlled, which is a key difficulty in the process. If the polyimide film is too thin, it may not provide sufficient insulation protection; if the polyimide film is too thick, it will increase the weight of the cable and affect performance. In addition, the wrapping process needs to be kept free of bubbles and defects to ensure the stability of electrical performance.

[0058] S3: A graphene shielding layer 3 is formed by wrapping a layer of graphene film on the outside of the polyimide insulating layer 2 by physical vapor deposition or electrostatic spraying process.

[0059] The graphene film is evenly coated on the surface of the polyimide insulation layer 2 by physical vapor deposition (PVD) or electrostatic spraying to form the shielding layer of the cable. The graphene film attachment process needs to be carried out under vacuum conditions to ensure its high density and high conductivity. The maintenance of the vacuum environment and the uniform deposition of the graphene film are the main challenges, and any surface defects or unevenness will affect the shielding effect. In addition, the high conductivity of the graphene material requires avoiding oxidation during the processing and deposition process to ensure its shielding performance.

[0060] S4: Adopting bonding technology or surface treatment process to coat the ceramic-based composite material on the outside of the graphene shielding layer 3 to form a ceramic-based composite material barrier layer 4.

[0061] The ceramic matrix composite barrier layer 4 is designed as a porous structure to improve the thermal barrier effect, while taking into account the lightweight requirements, which is suitable for the weight reduction goal of the spacecraft. The production process of the ceramic matrix composite barrier layer 4 has the following difficulties: the ceramic matrix composite barrier layer 4 uses ceramic matrix composite materials, and the uniform mixing of these materials needs to be precisely controlled to ensure that the material density and composition of each area are consistent. Ceramic materials have high hardness and brittleness, so they are prone to cracks and unevenness during the preparation process, and need to be strictly controlled during the mixing and molding process to avoid the formation of internal defects; the ceramic matrix composite material must be processed into an appropriate thickness and have a porous structure to improve the thermal barrier effect. This porous structure requires very precise processing technology to ensure that the size and distribution of the pores are uniform, otherwise it will affect the thermal insulation performance and mechanical strength. When realizing this structure, precise sintering and molding processes are often required. The ceramic matrix composite barrier layer 4 needs to be located between the shielding layer and the outer sheath, so the material must be able to be well combined with the materials of the graphene shielding layer 3 and the outer sheath. Ceramic materials have low bonding strength with other materials, so special bonding techniques or surface treatment processes (such as plasma treatment or chemical plating) are required to improve adhesion and ensure a strong bond between the layers.

[0062] S5: The Teflon material is processed into a Teflon outer sheath 5 by an extrusion molding process, and is wrapped around the outer side of the ceramic-based composite material barrier layer 4 .

[0063] The Teflon jacket needs to be thick enough to provide reliable physical protection while remaining lightweight. The difficulty of the extrusion process is how to accurately control the thickness of the jacket to minimize weight while providing mechanical protection. In addition, the Teflon material has a high viscosity and is prone to uneven flow during the extrusion process, requiring high-precision temperature and pressure control to ensure the quality and performance of the jacket.

[0064] S6: using an electrostatic spraying process to spray a black oxide material on the surface of the Teflon outer sheath 5 to form a black oxide material layer, and then applying a layer of nanostructured carbon-based material on the black oxide material layer to form a carbon-based material layer. The black oxide material layer and the carbon-based material layer constitute a low reflectivity extinction layer 6.

[0065] First, the black oxide material (Fe3O4) is sprayed on the surface of the outer sheath using an electrostatic spraying process. Through the action of electrostatic charge, the charged oxide particles are evenly sprayed onto the outer sheath with the opposite charge, forming a uniform, low-reflectivity coating to absorb the main incident light. Then a layer of nanostructured carbon-based material (such as graphene or carbon nanotubes) is applied on it. This layer can not only absorb the remaining light energy, but also reflect and scatter the incident light multiple times on a microscopic scale through its special nanostructure, thereby further reducing the reflectivity.

[0066] The difficulty lies in:

[0067] ① Uniformity of material formula: The uniform mixing of carbon-based material iron oxide needs to be precisely controlled, otherwise it will easily lead to unstable light absorption effect of the coating and affect the overall optical performance.

[0068] ② Accuracy of coating deposition process: When using PVD and electrostatic spraying processes, it is necessary to ensure that the coating material is evenly covered on the outer sheath surface under vacuum or specific electrostatic conditions. Any mistakes in this process may result in insufficient adhesion or uneven thickness of the coating.

[0069] ③Coating thickness control: The coating thickness needs to be strictly controlled between 50 and 150 nanometers, which is necessary to ensure the low reflectivity effect without adding too much weight.

[0070] The present invention uses carbon nanotubes as cable cores instead of traditional metal conductors. Compared with traditional cables, the cables of the present invention are significantly lighter and have higher strength and ductility. Depending on the cable design, replacing the copper core and radio frequency (RF) cladding in coaxial data cables with carbon nanotube cable cores can reduce the cable mass by 30% to 70%. In addition, the ductility of the carbon nanotube cable core is better than that of copper wire, allowing the cable to be made into a thinner and more durable form.

[0071] Experiments show that the performance of the cable does not significantly decrease under extreme temperatures of -100°C to +200°C; after 100,000 bending cycles, the ductility of the CNT conductor remains intact and the conductivity does not change significantly. Compared with traditional metal conductor cables, its life is extended by 30%-50%.

[0072] After the cable is reduced in weight, the launch cost of the space optical system is significantly reduced. For example, if the launch weight of 1 kg costs 20,000 US dollars, if the weight of the space cable is reduced by 50%, the cost of each launch can be saved by about 100,000 US dollars. In addition, the use of lightweight materials also increases the payload space and improves the efficiency of mission execution.

[0073] Through experiments and simulation analysis, the ductility of carbon nanotubes and the electromagnetic shielding ability of graphene make the cable perform significantly better than traditional cables in space missions. The two-dimensional structure of graphene can effectively shield electromagnetic radiation, and its electromagnetic interference attenuation can reach more than 80%, far exceeding the traditional metal shielding layer; in the temperature range of -100℃ to 200℃, the resistance of carbon nanotube cables only increases by about 20%~30%, while the resistance of traditional copper cables increases by 50%~80%, as shown in Table 2. In addition, in high radiation environments (such as radiation intensity of 100Gy / h), the electromagnetic shielding performance of carbon nanotubes and graphene materials is stable, and signal transmission is almost unaffected. Compared with the low reflectivity extinction layer 6, the reflectivity of the cable outer sheath is reduced from 5~15% to 2%, which effectively reduces the stray light caused by the cable surface and ensures the optical performance of the system.

[0074] Table 2 Comparison of resistance between carbon nanotube cables and copper cables at different temperatures

[0075]

[0076] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps described in the disclosure of the present invention can be performed in parallel, sequentially or in different orders, as long as the desired results of the technical solution disclosed in the present invention can be achieved, and this document does not limit this.

[0077] The above specific implementations do not constitute a limitation on the protection scope of the present invention. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An aerospace optical payload cable based on carbon-based materials, characterized in that: From the inside to the outside, it includes a twisted conductor, a polyimide insulation layer, a graphene shielding layer, a ceramic-based composite barrier layer, a Teflon outer sheath and a low-reflectivity extinction layer; wherein the twisted conductor includes a carbon nanotube cable core and a graphite-reinforced polymer cable core; the low-reflectivity extinction layer includes a black oxide material layer and a carbon-based material layer composed of a nanostructured carbon-based material located outside the black oxide material layer.

2. The aerospace optical load cable based on carbon-based materials according to claim 1, characterized in that: The black oxide material layer is Fe3O4, and the carbon-based material layer is graphene or carbon nanotubes.

3. The aerospace optical load cable based on carbon-based materials according to claim 1, characterized in that: The thickness of the black oxide material layer is 50nm~150nm.

4. A method for preparing a carbon-based material-based aerospace optical payload cable as claimed in any one of claims 1 to 3, characterized in that: The steps include: S1: Processing carbon nanotubes and graphite-reinforced polymers into yarn or sheet form and spirally winding them to form a stranded conductor; S2: A polyimide film is wrapped around the outside of the stranded conductor using a hot melt process to form a polyimide insulation layer; S3: A graphene shielding layer is formed by wrapping a layer of graphene film on the outside of the polyimide insulating layer by physical vapor deposition or electrostatic spraying process; S4: using bonding technology or surface treatment process to coat the ceramic-based composite material on the outside of the graphene shielding layer to form a ceramic-based composite material barrier layer; S5: The Teflon material is processed into a Teflon outer sheath by an extrusion molding process, and is wrapped around the outer side of the ceramic matrix composite barrier layer; S6: spraying a black oxide material on the surface of the Teflon outer sheath by an electrostatic spraying process to form a black oxide material layer, and then applying a layer of nanostructured carbon-based material on the black oxide material layer to form a carbon-based material layer.

5. The method for preparing aerospace optical load cables based on carbon-based materials according to claim 4, characterized in that: The number of carbon nanotubes and graphite-reinforced polymers is 10 to 20, respectively.

6. The method for preparing aerospace optical load cables based on carbon-based materials according to claim 4, characterized in that: The winding angle of carbon nanotubes and graphite-reinforced polymer is 25°~35°.

7. The method for preparing aerospace optical load cables based on carbon-based materials according to claim 4, characterized in that: During the winding process of the carbon nanotubes and the graphite reinforced polymer, a tensile prestress of 5 MPa to 20 MPa is applied to the carbon nanotubes and the graphite reinforced polymer.

8. The method for preparing aerospace optical payload cables based on carbon-based materials according to claim 4, characterized in that: The process parameters of the hot melt process are: hot melt temperature is 400°C, coating time is 30min, and pressure is 5MPa.

9. The method for preparing aerospace optical load cables based on carbon-based materials according to claim 4, characterized in that: The black oxide material is sprayed by physical vapor deposition or electrostatic spraying process under vacuum or specific electrostatic conditions.

Citation Information

Patent Citations

  • Large-section mineral-insulated multi-core branched fireproof cable

    CN105788733A

  • Full carbon light cable

    CN205881496U